Pemanfaatan Aplikasi Blogger Sebagai Media Promosi Jasa Dekorasi Pernikahan Pada Rahma Pelaminan - Zahara Odelia; Nova Dilastri; Soelarno Soelarno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The purpose of this study is to provide an understanding of the use of Blogger as a digital promotional tool for the wedding decoration service business "Rahma Pelaminan." The research method used a descriptive qualitative approach, with data collection techniques including observation, interviews, and direct documentation with the business owner's children. Blogger was chosen because it is easily accessible, low-cost, and has features that can be used to display the business profile, package list, decoration gallery, and booking contact information. Data collection tools used were a mobile phone for documenting evidence and writing tools such as pens for taking notes as needed for the research. The results show that the use of Blogger for Rahma Pelaminan can increase business visibility, expand promotional reach, and build Rahma Pelaminan's professional image. Furthermore, customers can more easily access comprehensive information about services and pricing without having to visit the location in person.